Digital Innovation Of People's Market In The Era Of Society 5.0 - Saputra, Ondy Asep; Jumanah, Jumanah; Ramdhan, Miftah Faiz Ali; Nugroho, Arif (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
The use of digital technology to improve traditional markets in the Society 5.0 era. This era is a continuation of Industry 4.0 and includes the use of technology to solve social problems and improve the quality of life of people. The study emphasizes the importance of combining digital technologies such as the Internet of Things (IoT), artificial intelligence, and robotics to create markets that are more efficient and responsive to consumer needs. Nowadays, people's markets are expected to serve not only as a place to trade but also as a hub for innovation that has the ability to boost local economic growth and improve public well-being. Traditional markets can enhance competitiveness with digitization through better management, price transparency, and broader access to markets. It is hoped that this transformation can help MSMEs and create a more inclusive and sustainable business environment.  To create a modern and highly competitive people's market in the era of Society 5.0, this study calls on all parties to adapt and innovate. This is because the adoption of technology in the people's market requires cooperation between governments, entrepreneurs, and society.